“My boss is 18,000 people”: Journalism practices in crowdfunded media organizations - Zaripova, Adilya (MedieKultur: Journal of media and communication research, 2017)
Imagine a media organization without ownership, hierarchy, advertisement, where every journalist is free to do whatever he or she wants. Recently, more and more journalists around the world have been chasing this beautiful dream. In the Netherlands, Germany, the United States, Hungary, Russia, Spain, journalists are attempting to create media solely or partly financed through crowdfunding. This article analyzes three crowdfunded media organizations in three different countries—Krautreporter (Germany), Direkt36 (Hungary), and Colta (Russia). Using qualitative, in-depth interviews, it demonstrates that journalism practices in a crowdfunded newsroom are very different from those in other media. The study concludes that direct funding from the audience is a burden in a practical sense: this business model is financially unstable and increases the amount of work that journalists have to do. At the same time, participants claim to be more satisfied with their work now than they ever were before.